Strengthening Teacher Well-Being through Fitness and Counseling Training: Community Engagement at Sekolah Indonesia Makkah - Abdul Hafidz; Lutfi Saksono; Syafi’ul Anam; Muhammad Sholeh; Muhammad Farid Ilhamuddin; Karwanto Karwanto (ABISATYA : Journal of Community Engagement, 2025)
Teacher well-being is a crucial determinant of educational quality, yet many educators particularly those working abroad. They face challenges that compromise their physical and psychological health. This community engagement program (PKM) conducted by Universitas Negeri Surabaya (Unesa) at Sekolah Indonesia Makkah (SIM), Saudi Arabia, aimed to enhance teacher wellness through integrated fitness and counselling training. Using a hybrid model that combined online lectures and offline practice, 23 teachers participated in structured physical exercise sessions, health education, and guidance and counselling workshops. Baseline assessments indicated that 78% of participants rarely engaged in exercise and 65% were dissatisfied with their physical condition. Post-intervention data revealed substantial improvements: 87% of teachers began exercising weekly, reported higher energy and motivation levels, and demonstrated greater awareness of wellness in teaching. Counselling competence also improved markedly, with 90% of participants able to apply preventive and developmental guidance strategies in classrooms. Qualitative feedback emphasized increased collegiality, emotional resilience, and a stronger sense of community, culminating in the establishment of a Teacher Fitness Club as a sustainable outcome. The study concludes that integrating physical and psychological well-being training strengthens teachers’ professional capacity, fosters holistic education, and exemplifies the transformative role of universities in global community partnership.